Use of uranium-thorium dating to determine past C-14 reservoir effects in lakes: examples from Antarctica - Hall, B; Henderson, G (2001)
The chronologies of many lacustrine records suffer from radiocarbon reservoir effects due to the presence of dissolved 'dead' carbon or to slow air-water exchange. Here we use the TIMS uranium-thorium disequilibrium method, in conjunction with AMS radiocarbon dating, to determine the age of lacustrine carbonates and to quantify the past radiocarbon reservoir effect in two Antarctic lakes with differing characteristics. By correcting a single-sample U/Th age for detrital contamination, a 14C offset of ~18 000 yr was obtained for carbonates from the former grounding line of the Ross Sea ice sheet in Glacial Lake Trowbridge. This large reservoir effect is believed to result from the direct input of old CO2 from glacial meltwater. In the second example, an isochron approach on coeval samples formed at the bottom of Lake Vida (now exposed due to lower lake level) yielded an age of 9550 ± 340 yr B.P. and a radiocarbon reservoir age of 3600 yr. This offset was probably the result of lack of aeration due to perennial ice cover and/or strong density stratification. This evidence for long-term isolation of the lake bottom indicates another level of hardship for life in the Dry Valley lacustrine environment - an environment studied as an analogue for extreme periods of Earth history, as well as for exobiological implications. The success of the U/Th technique on these two examples indicates that TIMS U/Th dating will be of widespread use in dating the important climate information recorded in the Dry Valleys both within and beyond the 14C age range. © 2001 Elsevier Science B.V. All rights reserved.